Personalized reading : digital strategies and tools to support all learners - Haiken, Michele; Furman, L. Robert (International Society for Technology in Education, 2018)
"Due to the diversity of readers in today's classrooms, teachers are called upon to teach not reading, but readers. Personalized Reading highlights four different types of readers -- the struggling reader, the reluctant reader, English learners and advanced readers -- and presents ways to use technology tools to accommodate their different reading styles. With this book, teachers will develop the skills they need to help students select their own texts, conduct reading workshops and teach students to read both print and visual texts, while identifying what works best for each student to maximize learning and potential. The strategies and classroom-ready ideas presented here will help educators incorporate technology to promote reading, critical thinking and digital literacy, and will answer questions like: How can teachers meet the needs of all learners to help them think critically and communicate effectively? How can teachers approach reading of visual, print and digital text? This book will: help teachers empower students with the skills and strategies they need for reading success, and to find joy in reading; inspire teachers to think beyond the text to help meet students where they are and raise the level of thinking about teaching readers; and provide activities and lessons to help support the diverse learners that enter the classroom, highlighting a variety of technology tools to tap into the multifaceted texts students can access"--